2011
DOI: 10.1523/jneurosci.0179-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

DNA Endoreplication in the Brain Neurons during Body Growth of an Adult Slug

Abstract: Endoreplication is DNA synthesis without cell division. Giant neurons observed in the brains of mollusks are thought to be generated as a result of DNA endoreplication. It has been hypothesized that neuronal size becomes larger in parallel with an increase in body size and that DNA endoreplication is involved in this process to meet the increasing demand for macromolecules in neurons. There is, however, no experimental evidence for this hypothesis to date. In the present study, we investigated the following qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…In some contexts, programmed polyploidy facilitates neuronal growth. For example, in the terrestrial slug Limax valentianus endoreplication occurs throughout the nervous system in proportion to animal growth, presumably to facilitate neuron expansion (Yamagishi et al, 2011). Neuronal polyploidy has been documented in vertebrates as well; tetraploid neurons exist in the retina and cortex (López-Sánchez and Frade, 2013;Morillo et al, 2010), and Purkinje neurons may be polyploid (Lapham, 1968;Mann et al, 1978).…”
Section: Endoreplication In Nervous System Developmentmentioning
confidence: 99%
“…In some contexts, programmed polyploidy facilitates neuronal growth. For example, in the terrestrial slug Limax valentianus endoreplication occurs throughout the nervous system in proportion to animal growth, presumably to facilitate neuron expansion (Yamagishi et al, 2011). Neuronal polyploidy has been documented in vertebrates as well; tetraploid neurons exist in the retina and cortex (López-Sánchez and Frade, 2013;Morillo et al, 2010), and Purkinje neurons may be polyploid (Lapham, 1968;Mann et al, 1978).…”
Section: Endoreplication In Nervous System Developmentmentioning
confidence: 99%
“…37 In contrast, neurons with an elevated degree of ploidy have been observed both in invertebrates and in lower vertebrates. 33,34 Polyploidization in these latter neurons takes place through successive endoreplicative cycles that seem to be abolished in higher vertebrates, in which neurons are maintained with 4C DNA content. Our results suggest that p27 Kip1 , a CKI known to prevent Cdk2 activity and block G1/S transition, 3,9,58 is likely involved in the mechanism that prevents tetraploid neurons to undergo successive rounds of endoreplication in the chick retina.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Somatic polyploid neurons generated by endoreplication are very common in the nervous system of lower vertebrates and invertebrates. 33,34 For instance, the nucleus of giant neurons from Aplysia californica has been shown to contain 200,000-fold the normal amount of haploid DNA (i.e., 200,000C). 33 These neurons have routinely been subjected to electrophysiological analyses, 35 proving that they are fully functional.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization of Limax nitric oxide synthase 2 (lim-NOS2), vesicular glutamate transporter (vGluT), light-yellow cell prepropeptide (LYCp), and achatin-I was performed as described previously (Matsuo and Ito, 2009;Yamagishi et al, 2011). The images of the sections were obtained with a BX-51 light microscope, equipped with a DP70 CCD camera and an objective (43, NA 0.16).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…We have recently reported that these brain neurons are generated as a result of repeated whole genome duplication (polyploidization) in a body growth-dependent manner using the gastropod slug Limax valentianus (Yamagishi et al, 2011Matsuo et al, 2012). However, it remains unclear what induces genome duplication in neurons when the slug's body grows, that is, what aspects of the body's growth are detected by neurons.…”
Section: Introductionmentioning
confidence: 99%